Delegation of patient related tasks to allied health assistants: a time motion study - David A Snowdon; Olivia A King; Amy Dennett; Jo-Anne Pinson; Michelle M Shannon; Taya A Collyer; Annette Davis; Cylie M Williams (BMC, 2022)
Abstract Background Allied health assistants (AHAs) are support staff who complete patient and non-patient related tasks under the delegation of an allied health professional. Delegating patient related tasks to AHAs can benefit patients and allied health professionals. However, it is unclear whether the AHA workforce is utilised optimally in the provision of patient care. The purpose of this study was to determine the proportion of time AHAs spend on patient related tasks during their working day and any differences across level of AHA experience, clinical setting, and profession delegating the task. Methods A time motion study was conducted using a self-report, task predominance work sampling method. AHAs were recruited from four publicly-funded health organisations in Victoria, Australia. AHAs worked with dietitians, occupational therapists, physiotherapists, podiatrists, social workers, speech pathologists, psychologists, and exercise physiologists. The primary outcome was quantity of time spent by AHAs on individual task-categories. Tasks were grouped into two main categories: patient or non-patient related activities. Data were collected from July 2020 to May 2021 using an activity capture proforma specifically designed for this study. Logistic mixed-models were used to investigate the extent to which level of experience, setting, and delegating profession were associated with time spent on patient related tasks. Results Data from 51 AHAs showed that AHAs spent more time on patient related tasks (293 min/day, 64%) than non-patient related tasks (167 min/day, 36%). Time spent in community settings had lower odds of being delegated to patient related tasks than time in the acute hospital setting (OR 0.44, 95%CI 0.28 to 0.69, P < 0.001). Time delegated by exercise physiologists and dietitians was more likely to involve patient related tasks than time delegated by physiotherapists (exercise physiology: OR 3.77, 95% 1.90 to 7.70, P < 0.001; dietetics: OR 2.60, 95%CI 1.40 to 1.90, P = 0.003). Time delegated by other professions (e.g. podiatry, psychology) had lower odds of involving patient related tasks than physiotherapy (OR 0.37, 95%CI 0.16 to 0.85, P = 0.02). Conclusion AHAs may be underutilised in community settings, and by podiatrists and psychologists. These areas may be targeted to understand appropriateness of task delegation to optimise AHAs' role in providing patient care.